Formulation and Characterization of Instant Powder Combination of Ginger, Bangle, and Lemon Extract as an Antioxidant - Aji, Nur; Sutiswa, Shandra Isasi (Universitas Airlangga, 2023)
Background: Degenerative disease is a decreasing organ function; clinical manifestations can affect the whole body, which is caused by oxidative stress. Ginger, bangle, and lemon have antioxidant properties. The combination of the three is expected to increase antioxidant activity. Objective: This study aimed to determine the potential antioxidant activity of the mixture of the three samples formulated as instant powder. Methods: This research is an experimental laboratory. This study will examine the effect of variations in extract concentration and PEG-40 HCO concentration on instant powder's characteristics and antioxidant activity. Results: Individually, ginger extract has extreme antioxidant activity (IC50 = 23.57 ± 0.13 µg/mL) and bangle strong (IC50 = 64.89 ± 0.15 µg/mL), while lemon has weak antioxidant activity (IC50 >500 µg/mL). Combining ginger, bangle, and lemon with a simplex axial method obtained the combination of ginger: bangle: lemon with the ratio of 4/6: 1/6: 1/6. Adding a mixture of extracts affects the solubility and antioxidant activity of the extracts. The greater the amount of extract, the lower the solubility, and the antioxidant activity did not increase with addition. The addition of PEG-40 HCO increases the solubility of the extract in the instant powder. Antioxidant activity increased to the